2022
DOI: 10.1371/journal.pone.0277646
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic screening of 1,953 FDA-approved drugs reveals 26 hits with potential for repurposing for Peyronie’s disease

Abstract: Drug repurposing has been shown to bring safe medications to new patient populations, as recently evidenced by the COVID-19 pandemic. We investigated whether we could use phenotypic screening to repurpose drugs for the treatment of Peyronie’s disease (PD). PD is a fibrotic disease characterised by continued myofibroblast presence and activity leading to formation of a plaque in the penile tunica albuginea (TA) that can cause pain during erection, erectile dysfunction, and penile deformity. PD affects 3–9% of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…In terms of fibroblast heterogeneity, this would have potential to a significant contribution to the fibrosis field, as we previously reported that exposure to the same FDA-approved drugs can lead to different levels of myofibroblast transformation or prevention thereof in various tissues, i.e. drugs that show significant inhibition in one tissue type show no inhibition in the other 87 , 88 . In addition, in the current study, we only tested one time point of adding the myofibroblast vesicles (co-incubated with TGF-β1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of fibroblast heterogeneity, this would have potential to a significant contribution to the fibrosis field, as we previously reported that exposure to the same FDA-approved drugs can lead to different levels of myofibroblast transformation or prevention thereof in various tissues, i.e. drugs that show significant inhibition in one tissue type show no inhibition in the other 87 , 88 . In addition, in the current study, we only tested one time point of adding the myofibroblast vesicles (co-incubated with TGF-β1).…”
Section: Discussionmentioning
confidence: 99%
“…Human primary fibroblasts were isolated from TA samples from patients undergoing corrective surgery for PD as previously described [88][89][90][91] . Tissue samples were transferred to the labs from the hospital in ice cold DMEM F-12 with 10% foetal calf serum (FCS) and 1% penicillin/streptomycin in less than 3 h. Once the tissue arrived in the lab, it was dissected and corpus cavernosum was removed.…”
Section: Isolation Of Fibroblastsmentioning
confidence: 99%
See 3 more Smart Citations